Pain education for clinicians in geriatrics: a study into changes in clinician attitudes and beliefs (Health Education in Practice: Journal of Research for Professional Learning, 2018)
A lack of recognition of chronic pain in older adults has fundamental healthcare implications. A practice gap exists that affects evidence-based practice for chronic pain assessment and management specific to older adults. Psychologically informed practice (PIP) has been proposed as a method of enabling health professionals to deliver biopsychosocial pain assessment and management in their practice. The aim of this study was to test the feasibility of a single one-day structured educational program to both introduce the concept of PIP and to shift the attitudes, beliefs and orientation towards patients of clinicians working in the geriatric rehabilitation setting. An observational pre-post study design used two previously validated questionnaires: Pain Attitudes and Beliefs Scale (PABS) and the Patient-Practitioner Orientation Scale (PPOS). Eighteen clinicians from a sub-acute geriatric rehabilitation hospital participated in a one-day pain education training workshop run by an expert psychologist who trains health professionals in pain management skills. Participants completed the questionnaires pre and immediately post workshop. A significant shift (p < 0.001) away from the biomedical model ( = -9.33, 95% CI: -12.41 to -6.26) was detected in the PABS post-workshop, indicating a change towards a more biopsychosocial attitude in assessing and treating chronic pain. Nil significant change ( = 0.61, 95% CI: -2.44 to 3.66) was detected in the PPOS. In conclusion, a one-day structured educational program was feasible in providing foundational steps in implementing the concept of PIP in geriatric rehabilitation settings. This was sufficient to shift key therapist attitudes and beliefs towards a more biopsychosocial model of pain management in older adults, and to reduce the strength of their biomedical attitudes. Surprisingly, this attitudinal shift was not accompanied by a shift in practitioner orientation towards their patients. Practitioner-patient orientation represents a potential translational target to improve the implementation of biopsychosocial principles in the care of the older adult.